Coal and the Environment: Some implications for South Africa - Makhombothi, Ntuthuko (University of the Witwatersrand, Johannesburg, 2024)
South Africa’s coal industry faces an existential threat from the need to transition to a low carbon economy. This study analyses the implications of the Just Energy Transition (JET) on the coal industry of South Africa using mixed methods approach and secondary data from industry reports, government reports and academic sources. The study demonstrates the significant economic contribution of coal to the GDP, employment and energy security, while evaluating the JET framework against international principles. Although the JET framework is largely aligned with international principles, there are some areas for improvement. The decommissioning of the Komati power station illustrates the shortcoming in the distributive, restorative and redistributive justice. The findings suggest a need for a balanced JET that ensures economic growth, energy security and environmental sustainability. Further research is required to develop transition pathways that mitigate against the negative socioeconomic consequences for coal dependent communities
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Just Energy Transition; Renewable Energy; Energy Security; Clean Coal technologies; Procedural Justice; UCTD; SDG-7: Affordable and clean energy